FIREARMS USED BY GERMANY, RUSSIA AND THE USA DURING THE TWO WORLD WARS AND THEIR DEVELOPMENT TRENDS (International journal of artificial intelligence, 2026)
This article analyzes the main small arms used by Germany, Russia (USSR) and the USA during the Second World War, their technical characteristics and combat use.